ANALISIS MODEL PENGELOLAAN PARIWISATA BERBASIS MASYARAKAT - La Ode Aris; Heddy Shri Ahimsa Putra; Pande Made Kutanegara (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
Community-based tourism (CBT) is one of the management models adopted by the Wakatobi Regency government in managing tourism. This paper examines the management of community-based tourism in Wangi-Wangi Island, Wakatobi Regency from 2006 to 2019 Data were obtained from various literatures by conducting literature studies and from field observations and interviews with the community. Meanwhile, the data analysis technique used was a qualitative data analysis with CBT perspective. The results of this study indicate that the CBT model is carried out in two types: (1) tourism management is carried out by landowners in which local community is not directly involved in the management of object; (2) tourism management is carried out by the government, in which the local community is directly involved in managing the tourist objects. The supervision of CBT model management is carried out by the government along with the community involved in tourist objects. The local community can feel directly the benefit of CBT model, either directly or indirectly involved.